2018
DOI: 10.1037/gpr0000144
|View full text |Cite
|
Sign up to set email alerts
|

The Making of Violent Extremists

Abstract: The authors outline a psychological model of extremism and analyze violent extremism as a special case of it. Their significance quest theory identifies 3 general drivers of violent extremism: need, narrative, and network. The theory asserts that the need for personal significance-the desire to matter, to "be someone," and to have meaning in one's life-is the dominant need that underlies violent extremism. A violence-justifying ideological narrative contributes to radicalization by delineating a collective cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 116 publications
5
116
0
7
Order By: Relevance
“…Why would some people be attracted to groups that are extreme and demand intense conformity? Research indicates that, under threat, individuals are attracted to well-defined and active groups with highly purposeful and moralistic ideologies (Fritsche et al 2013;Hogg et al 2007;Kruglanski et al 2018). Groups with ideologies that provide a clear purpose and moralistic call to action are attractive to potential recruits, especially those feeling threatened, as they provide unambiguous conviction; this conviction would help excite the same, basic, agency-based motivational processes that relieve distress for individuals outside of group settings (Jonas et al 2014; Kruglanski et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why would some people be attracted to groups that are extreme and demand intense conformity? Research indicates that, under threat, individuals are attracted to well-defined and active groups with highly purposeful and moralistic ideologies (Fritsche et al 2013;Hogg et al 2007;Kruglanski et al 2018). Groups with ideologies that provide a clear purpose and moralistic call to action are attractive to potential recruits, especially those feeling threatened, as they provide unambiguous conviction; this conviction would help excite the same, basic, agency-based motivational processes that relieve distress for individuals outside of group settings (Jonas et al 2014; Kruglanski et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can also happen in a group setting in response to collective threats, but in a nonviolent way, as in the case of self-immolation (Biggs 2005;Somasundaram et al 2016). A violence-justifying ideological narrative is needed to help shape expressions of self-sacrifice toward terrorism and other violence-inflicting acts for the sake of the group (Kruglanski et al 2018). Evidence suggests that specific scriptural passages help encourage violence (Bushman et al 2007), and religious beliefs have been found to play a key role in explaining religious extremism (Appleby 1999;Dawson 2018;Dawson & Amarasingam 2017;Wood 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In psychological research, a variety of terms have been used to describe an engagement with religion, such as religiosity (e.g., Gibbs and Crader, 1970; Diener and Clifton, 2002; Paloutzian, 2017), religious fundamentalism (Altemeyer and Hunsberger, 1992; Williamson, 2010; Liht et al, 2011), radicalism, or extremism (e.g., Simon et al, 2013; Webber et al, 2017; Kruglanski et al, 2018). These terms are sometimes used interchangeably, and sometimes contested (e.g., religious fundamentalism may be used by some scholars to refer to a rigid interpretation of scriptures, in contrast to religious extremism which is often associated with a particular political agenda).…”
Section: Moderate Vs Extreme Religiositymentioning
confidence: 99%
“…Moving away from over-simplified representations of religious groups as politically motivated, the presented framework offers a practical method to understand the multi-faceted nature of extremism. It aims to analyze religion at both a group and individual level, augmenting scholarly understanding of the religious dimensions that may be relevant to enable accurate predictions of violent extremism based on ideological narratives (Kruglanski et al, 2018). Even though the four dimensions of religious extremism that we present here are informed by prior research on extremism and religiosity, the model that we developed is tailored to the context of Indonesian Muslims and their religious movements.…”
Section: Applying the Modelmentioning
confidence: 99%
“…From the above perspective, we believe that discussing the issue of ensuring access for forced and regular migrants to healthcare services through eliminating language barrier is topical and timely. Health is one of the basic people's needs; inability to have these needs accommodated might lead to eventual marginalization of ethnic or migrant communities (Booth and Lynch, 2003), which in its tern may provide fruitful grounds for spreading extremists' ideas (Hales and Williams, 2018; Kruglanski et al., 2018).…”
Section: Introductionmentioning
confidence: 99%